The Relation between Vulva Hygiene and Leucorrhea Incidence at Senior High School 6 Bau-Bau - Munir, Nur Wahyuni; Taqiyah, Yusrah; Pangiron, Atier Ningsih (International Journal of Halal System and Sustainability https://jurnal.narotama.ac.id/https://www.spb.gba.gov.ar/campus/https://conference.trunojoyo.ac.id/https://ojs.ucp.edu.ar/https://libros.cimsur.unam.mx/https://ojs.stikesmucis.ac.id/http://medi, 2021)
Leucorrhea is all discharge from the genitalia which is not blood but is a clinical manifestation of various infections, malignancies, or benign tumors of the reproductive organs. Vulva hygiene is the behavior of maintaining the cleanliness of the reproductive organs, especially the vaginal area so it is one of the factors that influence the occurrence of leucorrhea. This study aims to determine the relationship between vulva hygiene and leucorrhea incidence at Senior High School 6 Bau-Bau. This research used a cross-sectional from June-July 2019. The data were collected using a questionnaire on 48 students of class XI at Senior High School 6 Bau-Bau using a consecutive sampling technique. Data analysis used the chi-square test with a significance level of α less than 0.05. The results showed that vulva hygiene was less than 60.4%, and leucorrhea incidence was 79.2%. This study concludes that there is a significant relationship between vulva hygiene and leucorrhea incidence in XI students at Senior High School 6 Bau-Bau (ρ-value = 0.0001). The vulva hygiene in students at Senior High School 6 Bau-Bau needs to be further improved because vulva hygiene greatly affects the health of the genitalia